2011
DOI: 10.1016/j.chroma.2010.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Application of a modified linear solvation energy relationship (LSER) model to retention on a butylimidazolium-based column for high performance liquid chromatography

Abstract: Previously, a new HPLC stationary phase based on n-butylimidazolium bromide was investigated using a linear solvation energy relationship (LSER) to systematically evaluate the intermolecular interactions between 32 test solutes and the stationary phase. The results and further comparisons with conventional reversed phase systems revealed that retention properties are similar to phenyl phases in both methanol/water and acetonitrile/water mixtures. In this work, the LSER model is extended by including the degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…[29][30][31][32][33][34][35] Capillary electrophoresis and NMR studies have revealed that under aqueous conditions, imidazolium cations interact with halophenols through p-p stacking. [36] Linear solvation energy relation (LSER) studies using neutral aromatics have confirmed that SCIL phases exhibit multimodal retention [37] and behaved somewhat like phenyl phases under reversed-phase conditions. [38] While ionic liquid-based chiral selectors have been used as additives in capillary electrophoresis, [39] as stationary phases in gas [40,41] and liquid chromatography, [42] most of this previous work has relied on ion-pairing or hydrogen-bonding secondary interactions.…”
Section: Introductionmentioning
confidence: 82%
“…[29][30][31][32][33][34][35] Capillary electrophoresis and NMR studies have revealed that under aqueous conditions, imidazolium cations interact with halophenols through p-p stacking. [36] Linear solvation energy relation (LSER) studies using neutral aromatics have confirmed that SCIL phases exhibit multimodal retention [37] and behaved somewhat like phenyl phases under reversed-phase conditions. [38] While ionic liquid-based chiral selectors have been used as additives in capillary electrophoresis, [39] as stationary phases in gas [40,41] and liquid chromatography, [42] most of this previous work has relied on ion-pairing or hydrogen-bonding secondary interactions.…”
Section: Introductionmentioning
confidence: 82%
“…10 pHÀpKa 1 þ 10 pHÀpKa and 10 pKaÀpH 1 þ 10 pKaÀpH respectively for acidic and basic solutes [78]. The new form of the LSER model was:…”
Section: Reversed-phase Modementioning
confidence: 99%
“…Apart from the conventional monocationic ILs, our group recently prepared several imidazolium dicationic ILs-based stationary phases exhibiting considerably high column efficiency under HILIC mode [11]. All the studies indicated that ILs-modified HPLC columns could retain a wide range of solutes through multimodal retention mechanism such as electrostatic, ionic, -and dipole interactions [17,18,24], and are enjoying increasing popularity as a promising class of HPLC stationary phases.…”
Section: Introductionmentioning
confidence: 98%